Generating a Core Set of Outcomes for Hospital-Based Violence Intervention Programs - Monopoli, W. John (Journal of interpersonal violence, 2021)
Hospital-based violence intervention programs (HVIPs) engage individuals who have experienced violent victimization in postmedical care programming, with the goal of reducing the incidence and impact of future injuries. Although there is some empirical support for HVIPs’ impact on violence and crime-related outcomes, proper impact assessment is limited by a lack of systematized research on outcomes that relate to the proximal goals and activities of the programs themselves. To address this critical gap, we conducted a two-stage Delphi method to elicit and prioritize these outcomes using the wisdom and experience of those who are engaged in service delivery (i.e., HVIP community-based practitioners, program coordinators, and embedded researchers; N = 79). Through this process, respondents prioritized outcomes related to posttraumatic stress symptoms, beliefs about aggression, coping strategies, and emotional regulation, which have not been consistently measured using validated or standardized tools. Results suggest that, rather than limiting program outcomes to those related to repeat violent injury or criminality, hospital- and community-based violence prevention programs seek to improve and measure mental health and socioemotional outcomes as a benchmark for healing and recovery after a violent injury. Prioritization of these outcomes broadens the definition of recovery to include psychosocial health and well-being. In addition, inclusion of these outcomes in effectiveness studies will serve to bolster the relevance of findings, and provide support for continued development and refinement of HVIP practice.